الضغوط النفسية وعلاقتها بقلق الموت لدى الأمهات الحوامل - غفران, شلالبة (University of Eloued جامعة الوادي, 2023)
تعالج الدراسة الحالية موضوع الضغوط النفسية وعلاقته بقلق الموت لدى النساء الحوامل، في بعض المؤسسات الاستشفائية للأم والطفل بولاية الوادي وبعض العيادات الخاصة لطب وجراحة النساء والتوليد، خلال السنة 2023م/2024م. اعتمدت الدراسة على المنهج الوصفي الارتباطي، وذلك باستخدام مقياسي؛ الضغوط النفسية لـ: ( فقيه العيد)، وقلق الموت لـ: (عبد الخالق)، اللذان تم التأكد من خصائصهما السيكو مترية (الصدق، والثبات) على عينة قوامها (30) فردا، تم اختيارهم بطريقة عرضية. تم تطبيق الأدوات في صورتهما النهائية على عينة تتكون من ( 38) امرأة حامل وبعد جمع البيانات وتبويبها تم معالجتها بالاستعانة (بالحزمة الإحصائية للعلوم الإجتماعية ) وباستخدام معامل ارتباط بيرسون تم التوصل إلى النتائج التالية: spss-22 ـــ توجد علاقة ارتباطية ذات دلالة احصائية قوية بين الضغوط النفسية وقلق الموت لدى الأمهات الحوامل. ـــ توجد علاقة ارتباطية ذات دلالة احصائية سالبة قوية بين الضغوط النفسية وقلق الموت لدى الأمهات الحوامل للمرة الأولى. ـــ توجد علاقة ارتباطية ذات دلالة احصائية قوية بين الضغوط النفسية وقلق الموت لدى الأمهات الحوامل لأكثر من مرة. Study summary: The current study addresses the issue of psychological stress and its relationship to death anxiety among pregnant women, in some hospital institutions for mother and child in El-Wadi state and some private clinics for obstetrics and gynecology, during the year 2023/2024. The study relied on the descriptive correlational method, using my scale; The psychological pressures of: (Faqih al-Eid), and the death anxiety of: (Abdul Khaleq), whose psychometric characteristics (honesty and stability) were verified on a sample of (30) individuals, who were selected in a cross-sectional way. The tools were applied in their final form on a sample of (38) pregnant women for the first time, and after data collection and tabulation, it was processed using (spss-22), and using Pearson's correlation coefficient, the following results were reached: - There is a strong statistically significant correlation between psychological stress and death anxiety among pregnant mothers. - There is a strong negative statistically significant correlation between psychological stress and death anxiety among pregnant mothers for the first time. - There is a strong statistically significant correlation between psychological stress and death anxiety among pregnant mothers more than once.
تخصص علم نفس